Sulfation of Heparan and Chondroitin Sulfate Ligands Enables Cell‐Specific Homing of Nanoprobes. Issue 7 (14th December 2022) - Mardhekar, Sandhya; Subramani, Balamurugan; Samudra, Prasanna; Srikanth, Priyadharshini; Mahida, Virendrasinh; Ravindra Bhoge, Preeti; Toraskar, Suraj; Abraham, Nixon M.; Kikkeri, Raghavendra
Abstract: Demystifying the sulfation code of glycosaminoglycans (GAGs) to induce precise homing of nanoparticles in tumor cells or neurons influences the development of a potential drug‐ or gene‐delivery system. However, GAGs, particularly heparan sulfate (HS) and chondroitin sulfate (CS), are structurally highly heterogeneous, and synthesizing well‐defined HS/CS composed nanoparticles is challenging. Here, we decipher how specific sulfation patterns on HS and CS regulate receptor‐mediated homing of nanoprobes in primary and secondary cells. We discovered that aggressive cancer cells such as MDA‐MB‐231 displayed a strong uptake of GAG‐nanoprobes compared to mild or moderately aggressive cancer cells. However, there was no selectivity towards the GAG sequences, thus indicating the presence of more than one form of receptor‐mediated uptake. However, U87 cells, olfactory bulb, and hippocampal primary neurons showed selective or preferential uptake of CS‐E‐coated nanoprobes compared to other GAG‐nanoprobes. Furthermore, mechanistic studies revealed that the 4, 6‐ O ‐disulfated‐CS nanoprobe used the CD44 and caveolin‐dependent endocytosis pathway for uptake. These results could lead to new opportunities to use GAG nanoprobes in nanomedicine. Abstract : Synthetic ligands for nanoprobes : GAG nanoprobes composed of synthetic heparan sulfate and chondroitin sulfate ligands give a broad picture of cell‐specific homing of nanoparticles and provide a novel opportunity for nanomedicine. Chondroitin sulfate E is a potential ligand for designing nanoprobes to target CD44‐overexpressed cancer cells and neurites.